Geostatistical Methods for Scaling - Zhang, Jingxiong; Atkinson, Peter; Goodchild, Michael F. (Scale in Spatial Information and Analysis, 2014)
Chapters 4 and 5 described variogram-and autocorrelation-based approaches to modeling scale, which are designed for geostatistical and lattice data, respectively. As mentioned toward the end of Chapter 5, this chapter seeks to describe geostatistical methods for scaling, whereas the next chapter addresses methods for scaling lattice data (e.g., various images or raster data).